2008
DOI: 10.1097/sla.0b013e318190eddc
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Patients With Colorectal Cancer Is Associated With Lymph Node Ratio

Abstract: The defined cut-off values of LNRs were strong independent prognostic factors for colorectal cancer patients and should be calculated for risk group stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
85
3
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(98 citation statements)
references
References 30 publications
(33 reference statements)
8
85
3
2
Order By: Relevance
“…Although the data were collected prospectively, the study was designed retrospectively, which may have introduced a selection bias. In addition, the prognostic significance of the LNR has been previously evaluated using different methodologies yielding varying results, particularly due to differences in the cut-off values used for grouping patients and heterogeneity of collected data [8][9][10][21][22][23] for colorectal cancer. For the practical use of the LNR as a prognostic variable, the most effective LNR cutoff values need to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the data were collected prospectively, the study was designed retrospectively, which may have introduced a selection bias. In addition, the prognostic significance of the LNR has been previously evaluated using different methodologies yielding varying results, particularly due to differences in the cut-off values used for grouping patients and heterogeneity of collected data [8][9][10][21][22][23] for colorectal cancer. For the practical use of the LNR as a prognostic variable, the most effective LNR cutoff values need to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The LNR, defined as the ratio of metastatic to examined LNs, has been shown to be useful in identifying prognostic subgroups within gastric and esophageal cancer patients [6,7] . The prognostic value of the LNR has also been demonstrated in colon and rectal cancer [8][9][10] . These previous studies have shown that the LNR can be used not only as a prognostic indicator, but also as a parameter for a more accurate stratification system than the metastatic LN absolute number-based staging system in colon and rectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a substantial body of literature suggests that the absolute number of lymph nodes removed, whether positive or negative, is independently correlated with survival [14,15]. Furthermore, a number of studies have examined the ratio of positive lymph nodes to total number of lymph nodes as a predictor of survival [16][17][18][19][20][21]. These studies show that the ratio of positive nodes to the total number of nodes removed and examined is more predictive of patient outcome than the number of nodes involved with tumor alone.…”
Section: Introductionmentioning
confidence: 99%
“…Hastalığın evresi sağkalımı belirleyen en önemli faktörlerden biridir (14,26,27). Çalışmamızda da hastalığın evresi ve sağkalım arasında korelasyon (p=0,003) tespit edilmiştir.…”
Section: Discussionunclassified
“…Lenf nodu oranı (LNR), metastatik lenf nodlarının çıkarılan total lenf nodlarına oranıdır (14,32). İlk defa gastrik kanserde araştırıl-mış ve lenf nodu tutulumu olan mide kanserli hastaların bazı subgruplarında önemli bir prognostik faktör olduğu gösterilmiştir (11).…”
Section: Discussionunclassified